Phylogenetic divergence between Rickettsia amblyommatis strains from Argentina - Sebastian, Patrick Stephan; Tarragona, Evelina Luisa; Saracho Bottero, Maria Noelia; Nava, Santiago (Elsevier, 2020)
The aim of this study was to investigate if there is a phylogenetic divergence of Rickettsia amblyommatis strains from different phytogeographic provinces of Argentina and South America. Therefore, ompA and ompB gene sequences of R. amblyommatis DNA detected in Amblyomma hadanii and Amblyomma neumanni ticks from the Yungas and Chaco phytogeographic provinces, respectively, were obtained. These sequences were compared with GenBank sequences from R. amblyommatis from different countries of the American continent. The analyses shown that ompA haplotypes of R. amblyommatis form two clusters which differ phylogenetically. Regarding to ompB sequences, three groups of R. amblyommatis strains were detected. It could be shown that strains of R. amblyommatis detected in A. hadanii from the phytogeographic province Yungas are phylogenetic different to them detected in A. neumanni from the phytogeographic province Chaco. Furthermore, it could be observed that strains detected in different tick species associated with different phytogeographic provinces of the American continent differ phylogenetically.